Alteration in chromogranin A, obestatin and total ghrelin levels of saliva and serum in epilepsy cases - Dag, Ersel; Aydin, Suleyman; Ozkan, Yusuf; Erman, Fazilet; Dagli, Adile Ferda; Gurger, Mehtap (Elsevier Science Inc, 2010)
This study was designed to measure the levels of chromogranin A (CgA), ghrelin and obestatin in serum and saliva (including CgA expression in healthy tissue) in epileptic patients to determine any significant differences between these patients and healthy controls. Samples were obtained from a total of 91 subjects: 10 newly-diagnosed primary generalized epilepsy (PGE) patients who had started treatment with valproic acid and phenytoin for seizure control; 18 PGE patients who were previously and currently receiving treatment with valproic acid and phenytoin for seizure control; 37 patients with partial epilepsy (PE) (simple, n = 17 or complex, n = 20) who had been and were still being treated with carbazebime for seizures; and 26 healthy controls. CgA immunoreactivity in healthy salivary gland was analyzed by immunohistochemistry and ELISA. The levels of CgA, total ghrelin and obestatin in serum and saliva were measured by ELISA. The results revealed that normal salivary gland produces its own CgA. Before treatment, CgA levels in saliva and serum were significantly greater in patients newly-diagnosed with PGE than controls. Ghrelin and CgA concentrations were also greater in PGE patients previously or currently treated with drugs, and in patients with simple or complex partial epilepsy (PE) previously or currently treated with drugs, than in healthy normal controls. In conclusion, salivary concentrations of CgA, ghrelin and obestatin were similar to their serum levels, so saliva might be a desirable alternative to serum for measuring these hormones because it is easy and painless to collect. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Salivary; Chromogranin A; Ghrelin; Obestain; Seizure